Villa Ancheta - Gregori, Marian Andrea S. (Animo Repository, 2022)
Villa Ancheta is a 96-page feature-length screenplay that aims to tackle the impact of unresolved intergenerational trauma on individuals and their lives using the narrative conventions of Gothic horror. The screenplay is also an attempt to explore how unresolved intergenerational trauma can be dealt with, and how so-called “generational curses” can be broken. The screenplay centers on Rebecca Campilan, an aspiring writer who is having trouble getting over the death of her recently deceased mother. Her hang-ups trap her in a mix of self-sabotage and doubt over her life, though she insistently avoids addressing it. However, when she gets assigned to do a piece on an ancestral house located in her fictional hometown of Dimayuga, Rebecca is convinced that this is the change she’s been waiting for. Excited by the opportunity, she takes the job. When Rebecca gets to the grand, yet strangely unnerving Villa Ancheta, what starts off as a mundane job turns into an unravelling of past and present secrets about the house, the Anchetas, and Rebecca herself. The project was conceptualized, developed, and written by the proponent. The entire screenplay was written using the free browser version of the screenwriting software WriterDuet. The proponent worked on the project alone and did not require the arrangement of film shoots or coordination with any crew or cast members. PDF format.